Effet Du Niveau Protéique Et Du Traitement Des Graines De Pois D’angole (Cajanus Cajan (L.) Huth, 1893) Sur La Croissance Du Poulet Local (Gallus Gallus Domesticus, Linnaeus 1758) En Côte d’Ivoire - Traore Beh; Orsot Bosso M’bolo Marcel Roland; Komara Moussa; Ouattara Siaka; Dofara Soro (European Scientific Journal, ESJ, 2018)
This paper focuses on evaluating the effect of heat treatment of pigeon pea grains as a source of protein and protein level on local chicken growth. To conduct this study, 135 locally grown one-day-old chicks of roughly equal weight were randomized into 9 groups of equal size. Each group was subdivided into five lots of 3 subjects that were housed in a boxing. Then, three types of treatment (roasting, steaming and drying) were applied to the grains. For each type of treatment, three different protein level foods were developed. Each batch of chicks was fed with a given food. The results showed significant interactions between the protein level and the nature of the heat treatment on the different parameters (PTT <α, PNP <α and PTT * NP <α). Food consumption decreased significantly with protein level and was lower for CG and CV foods. The average daily gain and the feed index of batches fed with CG and CV foods were the best. Depending on the protein level, those titrated at 13% achieved the best growth and feed efficiency. Despite a lack of significant effect of the protein level on protein digestibility, there was a slight drop in protein at a dose of 16%. The nature of the treatment, for its part, significantly influenced the digestibility of proteins.